2004
DOI: 10.1016/j.jacc.2004.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine pulmonary venous flow and restrictive foramen ovale in fetal hypoplastic left heart syndrome

Abstract: Prenatal PV flow patterns in HLHS identify the fetus at risk of severe LA hypertension at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(50 citation statements)
references
References 31 publications
3
47
0
Order By: Relevance
“…[13][14][15][16] Moreover, it has been demonstrated that in the fetus with left heart obstruction and RAS, there are changes in pulmonary venous flow patterns 13 associated with the need for emergent atrial septoplasty (EAS) in the newborn period. 10 In our experience, however, there is significant variability in the pulmonary venous flow patterns even among fetuses with RAS ultimately requiring EAS in the newborn period ( Figure 1). These observed differences led us to question: at what point along the spectrum of pulmonary venous flow alterations does the need for neonatal atrial septoplasty become most predictable?…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…[13][14][15][16] Moreover, it has been demonstrated that in the fetus with left heart obstruction and RAS, there are changes in pulmonary venous flow patterns 13 associated with the need for emergent atrial septoplasty (EAS) in the newborn period. 10 In our experience, however, there is significant variability in the pulmonary venous flow patterns even among fetuses with RAS ultimately requiring EAS in the newborn period ( Figure 1). These observed differences led us to question: at what point along the spectrum of pulmonary venous flow alterations does the need for neonatal atrial septoplasty become most predictable?…”
mentioning
confidence: 76%
“…Persistent mortality despite relief of RAS in these patients may be partly a result of muscularization of the pulmonary arteries and arterialization of the pulmonary veins because of chronic in utero pulmonary venous hypertension. 2,9,10 The high morbidity and mortality in this patient population, coupled with evidence that these infants have potentially irreversible histological changes in the small lung vessels, has led some centers to pursue in utero therapies to decompress the left atrium and improve interatrial left-to-right shunting in the fetus with HLHS and RAS. 11 Identification of the fetus with HLHS and RAS may now, therefore, affect perinatal management decisions as well as parental counseling.…”
mentioning
confidence: 99%
“…We and others have demonstrated that pulmonary venous Dopplers show reduced forward flow in early diastole and increasing reversed flow in atrial systole with increasing left atrial hypertension [132,133]. Altered pulmonary venous Dopplers with only forward flow in ventricular systole and reversed flow in atrial systole is associated with critical cyanosis after delivery necessitating truly emergent atrial septoplasty, whereas the presence of even a small amount of forward flow in early diastole may identify the fetus in whom intervention may not be necessary for several hours to days, if at all.…”
Section: Intervention For Restrictive or Intact Atrial Septum In The mentioning
confidence: 64%
“…For example, damage such as vascular dysplasia and macrovascular dysplasia may occur due to abnormal hemodynamics during the fetal period, resulting in severe pathological changes, including single ventricle defects and severe heart dysfunction, occurring, which may lead to mortality (5)(6)(7)(8)(9). In particular, previous studies have identified severe coarctation of the aorta or aortic atresia, causing dysplasia of the aortic arch or left ventricle (7); pulmonary atresia or tricuspid atresia with an intact ventricular septum, resulting in right ventricular dysplasia; Ebstein's malformation of the tricuspid valve, resulting in functional pulmonary atresia (6); and severe damage to the vascular bed of the fetal lung as forms of secondary damage (5,8,9). These may be avoided by in utero correction of primary defects, which may potentially preserve fetal development (10).…”
Section: Introductionmentioning
confidence: 99%